Development of land and water management plan based on geoinformation technique for Puincha watershed, Odisha - ROUT, P. K.; PAUL, J. C.; PANIGRAHI, B. (Journal of Soil and Water Conservation, 2017)
Geospatial Techniques like Remote Sensing (RS) and Geographical Information System (GIS) techniques were used for land and water management action plan for Puincha micro-watershed in Banki block of Cuttack district, Odisha (India). IRS IC, LISS III FCC satellite images and toposheet number 73H/7 together with field verification were used as the data source for the mentioned planning. The objectives of the present research work was to prepare the thematic maps of land use/ land cover, hydrogeomorphology, soil, slope and drainage using satellite imagery data and survey of India (SOI) toposheet and to integrate all these maps under GIS environment to prepare the water and land resource management plans for the study watershed. The study will be helpful in identification of sites for construction of different soil and water conservation structures like water harvesting structures, check dams, farm ponds, percolation tanks, nala bunds etc. Nine items were suggested under land resource action plan with specific sites, aerial locations and maps. The study will be helpful in sustainable development of the natural resources including soil and water of the watershed with the proper implementation of the proposed action plans.